Pelindungan Hukum Terhadap Pemegang Saham Perusahaan Tercatat Dalam Hal Diberlakukannya Suspensi Perdagangan Efek Oleh Bursa Efek Indonesia (Studi Kasus: PT Evergreen Invesco, Tbk (GREN) Tahun 2017) - Jessica Kandiawan; Christine S.T. Kansil (Jurnal Hukum Adigama, 2020)
A private company that went public by making a public offering is obliged to convey information to their shareholders and also the Capital Market supervisors. When a public company fails to perform their obligations, Indonesia Stock Exchange (IDX) as one of the Capital Market supervisors may impose sanctions in the form of trading suspension. However, up until this day there is no legal certainty regarding the time limit of a trading suspension. That means, a company can be suspended for years without a clear time limit and ends up getting forced delisting by IDX. Thus, there is a need of legal protection to the shareholders regarding the unlimited time of trading suspension as well as corporate responsibility in case of being forced delisting. The research method used is normative juridical. In Indonesia, the Law Number 8 of 1995 concerning the Capital Market and the regulations below it provided legal protection to shareholders by determining the principle of disclosure. Furthermore, when a company gets forced delisting, the board of directors of the company must take responsibility for their negligence which resulted in the trading suspension (principle of piercing the corporate veil). In addition, Article 61 Paragraph 1 of Law Number 40 of 2007 concerning Company Law, states that the shareholders have the right to sue the board of directors through a district court. Shareholders also have rights to have their shares valued and purchased at a fair price by the Company.